2021
DOI: 10.3390/cancers13071682
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Death Ligand-1 (PD-L1) Is an Independent Negative Prognosticator in Western-World Gallbladder Cancer

Abstract: Inhibition of the programmed cell death protein-1/ligand-1 (PD-1/PD-L1) axis has opened a new era in the treatment of solid cancers. However, there is no data on the expression and relevance of PD-L1 in Western gallbladder cancer (GBC). We assessed PD-L1 immunohistochemically in 131 GBC patients as Tumor Proportion Score (TPS), Immune Cell Score (IC) and Combined Positivity Score (CPS). Tumor cells expressed PD-L1 in a subset of 14.7% GBC patients at a TPS cut-off of 1%. Higher PD-L1 levels above 10% and 25% T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 56 publications
2
18
0
1
Order By: Relevance
“…Immune checkpoint blockade of the PD-1/PD-L1 axis has been proven to be effective in many kinds of tumors ( 8 ). However, a low proportion of PD-L1 overexpression (only 12% to 23%) ( 9 12 ), MMR protein deficiency (only 1.3%) ( 14 ), and MSI (less than 2%) ( 4 ) were identified in GBC tissue, all of which indicated that a significant proportion of GBC patients could not benefit from the immunotherapeutic strategies focusing on the PD-L1/PD-1 axis. Further exploring the B7-third group is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Immune checkpoint blockade of the PD-1/PD-L1 axis has been proven to be effective in many kinds of tumors ( 8 ). However, a low proportion of PD-L1 overexpression (only 12% to 23%) ( 9 12 ), MMR protein deficiency (only 1.3%) ( 14 ), and MSI (less than 2%) ( 4 ) were identified in GBC tissue, all of which indicated that a significant proportion of GBC patients could not benefit from the immunotherapeutic strategies focusing on the PD-L1/PD-1 axis. Further exploring the B7-third group is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that the peripheral blood levels of circulating hematologic and serum cytokines and MAGE1 might serve as potential cancer biomarkers (17)(18)(19). Albrecht et al (20) reported that there is limited evidence on the efficacy of PD-1 inhibitors combined with other chemotherapeutic agents for GBC. The authors also reported that PD-L1 is upregulated in tumors and immune cells in a subpopulation of advanced Western GBC, providing evidence that the TIGIT/CD155 axis is a novel immune checkpoint for complement therapy for GBC.…”
Section: Discussionmentioning
confidence: 99%
“…We evaluated a relatively large number of surgically resected GBCs and observed only a small subset of MSI-high GBC cases (1.3%), with no obvious clinicopathologic association. Several previous papers evaluated PD-1 expression in prognostic aspect of gallbladder cancers (46)(47)(48)(49)(50)(51), and one of the study reported association of MSI-H and PD-L1 expression (49). For precise evaluation of tumor infiltrating lymphocytes (TILs) and PD-L1 expression, TIL and PD-L1 expression should be evaluated mainly at the tumor-normal interphase, whole-section slides are required.…”
Section: Discussionmentioning
confidence: 99%